Zoom Conference: A Study of Students' Perception on the Academic Achievement during COVID-19 Pandemic - Sutiyono, Akhmad; Hastomo, Tommy (Universitas Islam Negeri Raden Intan Lampung, 2022)
In the pandemic era of Covid-19, the students must study from home through online platform. One of many new platforms used by the students during such pandemic era of Covid-19 was Zoom. Zoom is a cloud based application for video conference. Consequently, as one of many schools that cannot conduct offline learning, STKIP PGRI Bandar Lampung also used online learning. This research wanted to understand how online learning affected the STKIP PGRI Bandar Lampung students, regarding their academix achievement. The researchers used Cluster Random Sampling as a sampling technique to get the research sample. This research used questionnaires to collect the data. The questionnaires were given to and answered by 23 students from the second semester in STKIP PGRI Bandar Lampung. SPSS, consistency analysis, static analysis, and regression analysis were used as data collection technique and analysis. The results showed that Zoom can be used as an alternative educational platform, and this platform was an appropriate educational media at STKIP PGRI Bandar Lampung. The researchers concluded that STKIP PGRI Bandar Lampung students had a clear understanding and were ready to learn English using Zoom in the pandemic Covid-19 era